Environmental taxation in Europe: What does it depend on? - Concetta Castiglione; Davide Infante; Maria Teresa Minervini; Janna Smirnova (Cogent Economics & Finance, 2014)
The present work adds to the existing literature the analysis of the determinants of environmental taxation in European economies. Using a pooled panel data, we consider various groups of factors influencing environmental taxation referring to production and consumption, environmental performance and the quality of governance of European countries, taking into account their heterogeneity. We argue that in order to function, environmental taxation policy should rely on the virtuous interrelationship between economic development and institutional enforcement, which contributes to enhancing the process of environmental renaissance.
Keywords: H23; Q56; O52; O1; 330; externalities; redistributive effects; taxes and subsidies; environment and development; trade sustainability; accounting; Europe; economic development